TINOSPORA EXTRACT (TINOSPORA CRISPA (L.) MIERS.) ENCAPSULATION WITH SODIUM ALGINATE ISOLATED FROM BROWN ALGAE (SARGASSUM ILICIFOLIUM) - Samran,; Hr, Tanjung (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Brotowali (Tinospora crispa) is well known as a bitter medicinal plant and traditionally has been used to treat rheumatism, gout, bruise, and fever and also to stimulate appetite. The bitter flavor of Tinospora extract has influenced the patient's compliance in using the Tinospora extract, especially for the pediatric patients. Encapsulation was a coated process of drug using solid or liquid form of thin layer. The encapsulation process was used at the pharmaceutical and food industry to mask the bitter taste of product and protect the active ingredients from oxidation process. The study aims were to encapsulate the Tinospora extract with sodium alginate by drips method. Methods: Brown algae (Sargassum ilicifolium) were a resource of alginate acid. Brown algae were macerate using HCl 5% to produced alginate acid, and sodium alginate was obtained by adding Na2CO3 5% to alginate acid solution. The study revealed that sodium alginate resulted from brown algae isolation process was 19.98% of the wet weight of brown algae. The formula of Tinospora extract microencapsulation was design into three formulas with different sodium alginate concentrations (F1=0.5%, F2=1%, and F3=1.5%). Results: The microcapsule resulted from three formulas had the various weight of xerogel alginate but with similar diameter. Xerogel alginate weight of F1 was 1.98 g, F2 was 2.15 g, and F3 was 3.21 g. It can be concluded that the weight of xerogel alginate microcapsule and form of microcapsule were depended on the sodium alginate concentration. Conclusions: The xerogel alginate microcapsule was evaluated for pre-formulation test, and the results showed that the microcapsule met the requirements of pre-formulations parameters without the adding of lubrication compound. The hedonic organoleptics test revealed that the microencapsulation process was able to cover the bitter taste and odor of Tinospora extract.